MODEL PERENCANAAN KAPASITAS DI PT GI DIVISI FRAGRANCE - Sudrajat .; Bambang .; Dana Santoso (SINERGI, 2014)
This research focuses on MTO strategy in fragrance division of PT GI which has a number of workstations with multiple tools, resources and products profile. The aims are developing a mathematic model of capacity planning system and analyzing the maximum production capacity and flexibility of resources to meet demand. The method is using RCCP technique that consists of product-load profiles, bills of capacity and labors. Cluster technical of sampling and probability plot are used for measuring and analyzing the output of each process and validating the mathematic model of capacity plan in order to establish certain specific sources, especially those expected to be a potential barrier (potential bottleneck), is sufficient to cover the expected demand till one year ahead.